Lokakarya Pengintegrasian Konsep Pendidikan Karakter yang Berwawasan Kebhinekaan ke dalam Mata Pelajaran di Sekolah Menengah Pertama (SMP) di Kecamatan Narmada - Untung Waluyo; Sudirman; A. Hari Witono; Sudirman Wilian; Fahruddin (Jurnal Pengabdian Magister Pendidikan IPA, 2022)
There are two major issues that are suspected to be stumbling blocks to the successful implementation of character education in schools. First, the pattern of character education approaches in schools is still very varied because there are no benchmarks that can be used as parameters to measure the success of the implementation of character education. Second, teachers lack training pertaining to the implementation character education due to the absence of professional development provided by the education authority. In order to achieve a character education process that is in accordance with the design mandated by the National Character Development Policy 2010-2025, a comprehensive workshop activity is needed that can provide insight to junior high school teachers with procedures for implementing effective and efficient character education. Therefore, this community service activity is directed to train teachers in schools to master patterns or models of integrating character education into the fields of study they are capable of. This activity has been successfully implemented according to plan and the teachers have acquired skills on how to integrate character education into every learning material they are capable of. The follow-up impact of this activity is that teachers in the field of study can make new innovations in conveying the essence of character education holistically.